Tubular glassy carbon microneedles with fullerene-like tips for biomedical applications - Malik, Sharali; Kostakis, George E. (Beilstein Journal of Nanotechnology, 2022)
Glassy carbon, in general, is made by the pyrolysis of polymeric materials and has been the subject of research for at least fifty years. However, as understanding its microstructure is far from straightforward, it continues to be an area of active research. Glassy carbon adopts different allotropes depending on the hybridizations of the C–C bond, that is, sp, sp2, or sp3. Furthermore, a variety of short-range ordering effects can interact with each other and this, along with the effects of microporosity, grain boundaries, and defects, render this a fascinating material. Following the nanoarchitectonics concept of bottom-up creation of functional materials, we use methane rather than a polymer to form glassy carbon. Here we show that tubular glassy carbon microneedles with fullerene-like tips form when methane undergoes pyrolysis on a curved alumina surface. X-ray diffraction of these glassy carbon tubules shows long-range order with a d-spacing of 4.89 Å, which is indicative of glassy carbon. Raman spectroscopy shows the material to be graphitic in nature, and SEM shows the fullerene-like structure of the material. This work provides new insights into the structure of glassy carbons relevant to the application of glassy carbons as a biomaterial, for example, as a new form of carbon-based microneedles. Since metallic needles can introduce toxic/allergenic species into susceptible subjects, this alternative carbon-based microneedle form has great potential as a replacement biomedical material for metallic needles in the field of neural engineering and as acupuncture needles.
Keywords: biomedical; glassy carbon; microneedle; neural engineering; COST Action EsSENce CA19118